The Closed Circle: Joining and Leaving the Muslim Brotherhood in the West - Vidino, Lorenzo (Columbia Studies in Terrorism and Irregular Warfare, 2020)
Frontmatter -- Contents -- Preface and Acknowledgments -- Abbreviations -- CHAPTER I. What Is the Muslim Brotherhood in the West? -- CHAPTER II. Joining and Leaving the Brotherhood -- CHAPTER III. Kamal Helbawy -- CHAPTER IV. Ahmed Akkari -- CHAPTER V. Pierre Durrani -- CHAPTER VI. Mohamed Louizi -- CHAPTER VII. Omero Marongiu -- CHAPTER VIII. Pernilla Ouis -- CHAPTER IX. The American Brothers -- CHAPTER X. Joining and Leaving -- CHAPTER XI. The Western Brotherhood’s Future -- Notes -- Bibliography -- Index